Concurrence of Papillary Thyroid Carcinoma and Hürthle Cell Carcinoma in an Iranian Woman with Hashimoto's Thyroiditis - Fatemeh Samiee Rad; Sohayla Farajee; Erfan Torabi (Iranian Society of Pathology, 2019)
The most usual form of the endocrine carcinoma is thyroid cancer (TC). In addition to papillary thyroid carcinoma (PTC), recent studies revealed incidence of RET/PTC rearrangement in other tumors, like Hürthle cell carcinoma (HCC) and even in non-carcinomatous disorders like Hashimoto's thyroiditis. Here, we present a case with concurrence of papillary thyroid carcinoma and Hürthle cell carcinoma. A 60-year-old woman referred to our hospital with a mass in her neck. Physical examinations revealed painful swelling in the thyroid. Ultrasonographic examination showed two hypoechoic nodules in the right lobe. Hürthle cell variant papillary carcinoma was suggested in the cytology report of the fine needle aspiration. Permanent histopathological diagnosis was co-existence of papillary thyroid carcinoma and Hürthle cell carcinoma. The patient was asymptomatic in 14 months follow up. Concurrence of papillary carcinoma and Hürthle cell carcinoma is a rare form of thyroid malignancies, with doubtful cytogenetic findings and biological behaviors. The results showed that it is necessary for the surgeons and pathologists to be aware of lesions for the optimal diagnostic and therapeutic interventions. Also, it is vital to follow up patients with the Hashimot's thyroiditis who have multiple nodules to detect occult thyroid cancers and decide for better therapeutic programs.